ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA BERDASARKAN LANGKAH-LANGKAH POLYA SISWA SMPN1 RASAU JAYA PADA MATERI ARITMATIKA SOSIAL - Abror, Ali Marwan (Bahasa Indonesia, 2023)
This qualitative descriptive study aims to describe the ability to solve mathematical problems in social arithmetic material. The subjects of this study consisted of 4 grade VII students of SMPN 1 Rasau jaya. Data collection techniques using tests and interviews. The results showed that indicator 1 of the subject was at level 3, which means students are able to carry out the stages of understanding the problem, preparing a settlement plan, and the stage of implementing a settlement plan. In indicator 2 subjects are at level 3. In indicator 3 subjects are at level 3. In indicator 4 subjects are at level 4 which means students are able to carry out the stages of understanding the problem, compiling a settlement plan, implementing a completion plan, and re-examining stage. So in general it can be concluded that the problem solving ability of class VII SMPN 1 Rasau Jaya is moderate.